Determining the boundaries of migratory bird flyways: a Bayesian model for Eurasian teal Anas crecca in western Europe. (3rd October 2017) - Guillemain, Matthieu; Calenge, Clément; Champagnon, Jocelyn; Hearn, Richard
Abstract : Accurate flyway delineation is a prerequisite for effective conservation and management of migratory bird populations, yet such limits have so far mostly been set subjectively. We present a statistical method to infer population boundaries from the analysis of ring recoveries, using a Bayesian framework. The approach was applied to Eurasian teal Anas crecca ringed in Camargue, southern France, and Abberton Reservoir, Essex, eastern England. The results presented show the boundaries of the two teal flyways in western Europe, with a zone of overlap, broadly matching those previously defined. The percentage of teal switching flyways (abmigration rate) was 2.4–2.6%, greater in birds ringed as juveniles than as adults. Abmigrants ended up at sites within the other flyway where the density of local birds was lower than expected by chance, suggesting abmigration resulted from exploratory or aberrant behaviour. The methodology presented here can be used to infer flyway boundaries of any bird with an adequate ring‐re‐encounter dataset, which has crucial consequences for the evaluation of their trends in abundance and hence conservation status, and the management of sustainable harvests.